Jasad-jasad samawi dalam al-Kutub al-Sittah: Ke arah pembangunan modul pembelajaran astronomi Islam / Ahmad Irfan Ikmal Hisham - Ahmad Irfan Ikmal , Hisham (2019)
Islamic astronomy has its learning system history since the revelation day. Prophet Muḥammad offered a lot of guidance, rather simplistically and descriptively, but full of motivation and progressive advice for future, often narrated in ḥadīths. Past studies have shown that there are relations between Islamic astronomy learning system and ḥadīth, with a parallel development. However, ḥadīth has often misunderstood from scientific, contextual, and referral context, due to the lack of knowledge possession among student and practitioner. Therefore, this research aims to construct the framework of learning module related to ‘ulūm al-ḥadīth to be embedded in Islamic astronomy learning system. This study engages qualitative approach, with library and field research as the primary methodology to get essential data, including the history of Islamic astronomy learning system based on the development of fiqh al-ḥadīth, and the compilation of ḥadīth on celestial bodies. Inductive and deductive methodologies were engaged with focusing on the thematic analysis in developing the theme of ḥadīth on celestial bodies. Fieldworks were conducted through structured and semi-structured interview with experts and practitioners for data validity. As a result from thematic analysis of ḥadīth on celestial bodies in al-Kutub al-Sittah, including analysis on tarājīm al-bāb on Islamic astronomy application, and issues that can only be understood through intervention of ‘ulūm al-ḥadīth, the researcher found that there are seven learning outcomes need to be embedded in the framework of module on ḥadīth for Islamic astronomy learning system.